Evaluasi Penggunaan Obat Mood Stabilizer pada Pasien Bipolar Rawat Jalan di Rumah Sakit Jiwa di Kota Padang - Dian Ayu Juwita; Fatma Sri Wahyuni; Fatiyah Nurazizah (Journal of Pharmaceutical and Sciences, 2026)
Bipolar disorder is a chronic psychiatric condition that requires long-term pharmacotherapy to control symptoms and prevent relapse. Mood stabilisers play a central role in its management; however, inappropriate use may reduce treatment effectiveness and increase the risk of adverse outcomes. This study aimed to evaluate the appropriateness of mood stabiliser use among outpatients with bipolar disorder at a psychiatric hospital in Padang City. This retrospective descriptive study used medical record data from January to December 2023. A total of 28 patients who met the inclusion criteria were included, with 220 outpatient visits analysed. Data collected included sociodemographic characteristics, clinical conditions, and medication use. The appropriateness of therapy was assessed based on four criteria: indication, patient suitability, drug selection, and dosage, using established pharmacotherapy guidelines as the reference standard. The results showed that most patients were female (78.57%) and aged 18–59 years (75%). The evaluation of drug use demonstrated that the appropriateness of indication, patient suitability, and drug selection each reached 83.18%. However, dosage appropriateness was considerably lower at 54.55%, indicating that nearly half of the prescriptions involved suboptimal dosing. While most aspects of mood stabiliser use were generally appropriate, dosing remains a critical issue that may affect treatment effectiveness and patient safety. These findings highlight the importance of improving adherence to clinical guidelines and conducting regular evaluations of pharmacotherapy to optimise outcomes in patients with bipolar disorder.